2001
DOI: 10.3346/jkms.2001.16.5.579
|View full text |Cite
|
Sign up to set email alerts
|

GenotypingCagA,VacAsubtype,IceA1, andBabAofHelicobacter pyloriisolates from Korean patients, and their association with gastroduodenal diseases

Abstract: The genetic status of cagA, vacA subtype, iceA1, and babA, and the relationship to gastroduodenal diseases were assessed in Helicobacter pylori isolates in Korea. Seventy-six strains of H. pylori were isolated from the antrum and the corpus of 41 adult patients (22 with peptic ulcer and 19 with gastritis). The cagA, iceA1, and babA genes were assessed by polymerase chain reaction and the vacA subtypes were determined by reverse hybridization-line probe assay. The positive rates of 349-bp cagA, 208-bp cagA, ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
51
15
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 30 publications
(28 reference statements)
21
51
15
4
Order By: Relevance
“…In an attempt to detect association between the cagE gene and PU, In contrast to the results reported in China, Japan, Korea and Netherlands where the iceA1 gene was predominant (16,20,31), the iceA2 gene was detected to be predominant genotype in this study. This result is in agreement with previous reports that the iceA2 gene was found to be prevalent in Brazilian, European and American patients (1,20,22).…”
Section: H Pylori Genotypescontrasting
confidence: 54%
See 1 more Smart Citation
“…In an attempt to detect association between the cagE gene and PU, In contrast to the results reported in China, Japan, Korea and Netherlands where the iceA1 gene was predominant (16,20,31), the iceA2 gene was detected to be predominant genotype in this study. This result is in agreement with previous reports that the iceA2 gene was found to be prevalent in Brazilian, European and American patients (1,20,22).…”
Section: H Pylori Genotypescontrasting
confidence: 54%
“…Our results were similar to a previous study (1) (12,19,29) while it was 80-100% in Asian countries (16). We found a higher prevalence (62.1%) of babA2 than the result (53.8%) reported in a previous study (10) in Turkey.…”
Section: H Pylori Genotypescontrasting
confidence: 48%
“…One of the most important virulence factors of H. pylori is cagA that is present in about 60-70 % of the Western strains and in more than 90 % of the East Asian ones [7, 28,29]. In our study cagA genotype, albeit determined by real-time PCR using two different sets of primers, was identified in only 31.8 % of isolates.…”
Section: Discussionmentioning
confidence: 49%
“…The H. pylori vacA s1m1 genotype is the most common in American, European and East Asian countries [24,29,[41][42][43]. The vacA s2m2 genotype is apparently less common and another study in Portugal, performed in patients submitted to a screening program, revealed a prevalence of 29.7 % for such allele combination (42.9 % if multiple vacA genotypes were excluded).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cagA and the vacuolating cytotoxin (vacA) genotypes are proposed to serve as predictors for progression of gastric lesions (Gonzalez et al, 2011). Moreover, presence of other genes of H pylori such as iceA (induced by contact with epithelium), oipA (outer inflammatory protein), and babA (blood group antigenbinding adhesin), has been reported to be associated with development of gastroentric disorders (Kim et al, 2001;Markovska et al, 2011). Most of these genes encode the proteins that help H pylori interact with host or change host cellular homeostasis, which ultimately lead to abnormalities like neoplastic tissues (Ilver et al, 1998;Naumann, 2005).…”
Section: Introductionmentioning
confidence: 99%